Low Serum Vitamin B-12 Concentrations Are Prevalent in a Cohort of Pregnant Canadian Women. Issue 5 (13th April 2016) - Visentin, Carly E; Masih, Shannon P; Plumptre, Lesley; Schroder, Theresa H; Sohn, Kyoung-Jin; Ly, Anna; Lausman, Andrea Y; Berger, Howard; Croxford, Ruth; Lamers, Yvonne; Kim, Young-In; O'Connor, Deborah L
Abstract: Background: Among Canadian women of reproductive age, 5% and 20% have serum vitamin B-12 concentrations indicative of deficiency (<148 pmol/L) and marginal status (148–220 pmol/L), respectively. Given the association between suboptimal vitamin B-12 and adverse pregnancy outcomes, an understanding of vitamin B-12 status during pregnancy, and factors that influence it, is required. Objective: This prospective analysis from the PREFORM (PREnatal FOlic acid exposuRe on DNA Methylation in the newborn infant) study investigated 1 ) vitamin B-12 status in a cohort of Canadian pregnant women and their newborns, 2 ) the association of maternal dietary vitamin B-12 intake with maternal and cord blood concentrations of vitamin B-12 and its biomarkers, and 3 ) the association of fetal genetic polymorphisms with cord blood concentrations of vitamin B-12 and its biomarkers. Methods: In pregnant Canadian women ( n = 368; mean ± SD age: 32 ± 5 y), vitamin B-12 intakes were assessed in early (0–16 wk) and mid- to late (23–37 wk) pregnancy. Serum vitamin B-12 and plasma total homocysteine (tHcy) and methylmalonic acid (MMA) in maternal blood at 12–16 wk of pregnancy and at delivery (28–42 wk) and in cord blood were measured and compared by using regression analyses. The associations of 28 fetal genetic variants in vitamin B-12 metabolism and cord blood vitamin B-12, tHcy, and MMA concentrations were assessed by using regression analysis, with adjustment for multiple testing. Results: A total of 17% and 38% of women had deficient and 35% and 43% had marginal serum vitamin B-12 concentrations at 12–16 wk of pregnancy and at delivery, respectively. Only 1.9–5.3% had elevated MMA (>271 nmol/L), and no women had elevated tHcy (>13 μmol/L). Maternal dietary vitamin B-12 intake during pregnancy was either weakly associated or not associated with maternal and cord blood vitamin B-12 ( r 2 = 0.17–0.24, P < 0.0008), tHcy ( P = NS) and MMA ( r 2 = 0.05–0.11, P < 0.001). Fetal genetic polymorphisms were not associated with cord blood concentrations of vitamin B-12 and its biomarkers. Conclusions: Deficient and marginal serum vitamin B-12 concentrations are prevalent in Canadian pregnant women with the use of traditional cutoffs, despite supplement use. Given the growing interest among women to adhere to a vegetarian diet that may be lower in vitamin B-12, and vitamin B-12's importance in pregnancy, the functional ramifications of these observations need to be elucidated. This trial was registered at clinicaltrials.gov as NCT02244684.